Intrinsic and extrinsic motivation the search for optimal motivation and performance - Sansone, Carol; Harackiewicz, Judith M. (San Diego : Academic Press, 2000)
In understanding human behavior, psychologists have long been interested in what motivates specific actions. Debates have pitted extrinsic motivators (e.g. rewards/punishment) against intrinsic motivation in attempting to determine what best motivates individuals. This book provides a summary view of what research has determined about both extrinsic and intrinsic motivation, and clarifies what questions remain unanswered. Divided into three sections, section I revisits the debate about the effects of extrinsic incentives or constraints on intrinsic motivation and creativity, and identifies theoretical advances in motivational research. Section II focuses on the hidden costs and benefits of different types of achievement goals on motivation and performance. Section III discusses theory and research findings on how extrinsic and intrinsic motivators may work in everyday life and over time. This book is of interest to researchers in psychology, education, and business, as well as to a wider audience interested in promoting optimal motivation and performance. Coverage in this book includes: debates and controversies in motivational research; developmental nature of intrinsic and extrinsic motivation over time; influences of parents, educators, and employers in facilitating motivation; effect of achievement goals on learning and performance; the role of intrinsic and extrinsic motivation in self-regulation. Key features: brings together major figures in the fields of motivation, education, and social psychology; provides a mix of theory, basic and applied research; presents research conducted both in laboratories and educational settings; comprehensive chapters provide excellent reviews of previous literature as well as outlines important new directions; and provides different perspectives on controversial debates in a balanced, constructive manner.
C. Sansone and J.M. Harackiewicz, Looking Beyond Rewards: The Problem and Promise of Intrinsic Motivation. -- Are the Costs of Rewards Still Hidden: A New Look at an Old Debate: -- R.M. Ryan and E.L. Deci, When Rewards Compete with Nature: The Undermining of Intrinsic Motivation and Self-Regulation. -- B.A. Hennessey, Rewards and Creativity. -- J.M. Harackiewicz and C. Sansone, Rewarding Competence: The Importance of Goals in the Study of Intrinsic Motivation. -- J.Y. Shah and A.W. Kruglanski, The Structure and Substance of Intrinsic Motivation. -- A New Debate: Hidden Costs (and Benefits) of Achievement Goals: -- D.C. Molden and C.S. Dweck, Meaning and Motivation. -- R. Butler, What Learners Want to Know: The Role of Achievement Goals in Shaping Information Seeking, Learning, and Interest. -- E.A. Linnenbrink and P.R. Pintrich, Multiple Pathways to Learning and Achievement: The Role of Goal Orientation in Fostering Adaptive Motivation, Affect, and Cognition. -- K.E. Barron and J.M. Harackiewicz, Achievement Goals and Optimal Motivation: A Multiple Goals Approach. -- The Role of Interest in Learning and Self-Regulation: "Extrinsic" versus "Intrinsic" Motivation Reconsidered: -- M.R. Lepper and J. Henderlong, Turning "Play" Into "Work" and "Work" Into "Play": 25 Years of Research on Intrinsic Versus Extrinsic Motivation. -- S. Hidi, An Interest Researcher's Perspective: The Effects of Extrinsic and Intrinsic Factors on Motivation. -- C. Sansone and J.L. Smith, Interest and Self-Regulation: The Relation Between Having to and Wanting to. -- K.A. Renninger, Individual Interest and its Implications for Understanding Intrinsic Motivation. -- J.E. Jacobs and J.S. Eccles, Parents, Task Values, and Real-Life Achievement-Related Choices. -- Part 4: Conclusion: -- C. Sansone and J.M. Harackiewicz, Controversies and New Directions - is it Deja Vu All Over Again? -- Index.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Motivation in education; Motivation (Psychology); Electronic books